You need to take logarithms both sides such that:

`ln y = ln((sin x)^(ln x)) `

Using logarithmic identites yields:

`ln y = ln x*ln sin x `

You need to differentiate both sides with respect to x such that:

`(1/y)*y' = (ln x*ln sin x)'`

You should use product rule to the right side such that:

`(1/y)*y' = (ln x)'*ln sin x + (ln x)*(ln sin x)'`

`(1/y)*y' = (1/x)*ln sin x + (ln x)*(1/sin x)*(sin x)'`

`(1/y)*y' = (1/x)*ln sin x + (ln x)*(cos x/sin x)`

`(1/y)*y' = (1/x)*ln sin x + (ln x)*(cot x)`

`y' = y*((1/x)*ln sin x + (ln x)*(cot x))`

Substituting `(sin x)^(ln x) ` for y yields:

`y' = ((sin x)^(ln x))*((1/x)*ln sin x + (ln x)*(cot x)))`

**Hence, differentiating the given function, using logarithmic differentiation, yields `y' = ((sin x)^(ln x))*((1/x)*ln sin x + (ln x)*(cot x))).` **

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now